2015
DOI: 10.1007/s11010-015-2594-9
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of carbon dioxide (CO2) in generation of reactive oxygen species

Abstract: The results testify to the fact that CO2 is a powerful inhibitor of reactive oxygen species (ROS) generation by cells (blood phagocytes and alveolar macrophages of 96 people and cells of inner organs and tissue phagocytes (of liver, brain, myocardium, lungs, kidneys, stomach, and skeleton muscles), as well as by mitochondria of the liver of 186 white mice and human tissues. Generation of ROS was determined using various methods with CO2 directly acting on the cells and bioptates and indirectly on the organism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…It is pointed out that Dogliotti et al (2011) have shown a depression of free radical release and elevation of the total antioxidant status upon immersion of lower legs of patients with peripheral occlusive disease in CO 2 -enriched water. In fact, CO 2 has been found to be a potent inhibitor for the generation of reactive oxygen species by different types of cells (Bolevich et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is pointed out that Dogliotti et al (2011) have shown a depression of free radical release and elevation of the total antioxidant status upon immersion of lower legs of patients with peripheral occlusive disease in CO 2 -enriched water. In fact, CO 2 has been found to be a potent inhibitor for the generation of reactive oxygen species by different types of cells (Bolevich et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…After the initial decrease of ADMA concentrations, we observed an increase within 24 hours after the CO 2 treatment, which may be due to a rebound effect explained by the subsiding of the vasodilator effect. In a recent study, Bolevich et al have proved that CO 2 is "a universal inhibitor of oxidative stress" (18). Reduced oxidative stress results in an increased efficiency of DDAH leading to decreased ADMA levels (16).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated carbon dioxide gas was used to inhibit formation of superoxide by NADPH oxidases [ 34 ]. Here, seeds of Poa annua , Poa reptans , Festuca arundinacea , Oryza sativa , Tritichum aestivum and Solanum lycopersicum were planted into potting mix or agarose in magenta boxes.…”
Section: Methodsmentioning
confidence: 99%